A Study of Economic and Ecological Strategies for Sustainable Development in Aceh, Indonesia - Zulkarnaen, Iskandar; Saputra, Jumadil; Abdurrahman, Fauzi; Suzanna, Ella (International Journal of Engineering and Technology, 2018)
The sustainable development becomes an inevitable paradigm today. It does not only concentrate on economic growth, but also pay attention to other issues on environmental sustainability such as justice, welfare, as well as the maintenance of social and cultural systems. The sustainable development has some indicators and should also proceed with a series of stages namely economic, ecological, political and social culture. Using qualitative data analysis, this study is written to identify whether or not the economic and ecological development in Aceh post-tsunami has met standards of sustainable development. Troubleshooting analysis is performed with statistical studies of a variety of documents compared to some facts and the evolving dynamics in the community that were recorded by media. Based on the central of statistics bureau, Aceh is one of the regions with the highest GDP in Indonesia and there are approximately 6 million hectares of forest and also rich in nature and marine resources. The result of this study shows Acehnese people actually trapped in poverty. It is very ironic because the majority of people are living in the location of natural resources such as forests and coastal areas, as well as natural gas industrial areas. Therefore, the Aceh Government should ensure the welfare of Acehnese people through an optimizing the utilization of the natural resources i.e. forest and coastal and also gas industry.Â Â